Circulating melanoma cells and survival in metastatic melanoma - RAO, C; BUI, T; CONNELLY, M; DOYLE, G; KARYDIS, I; MIDDLETON, M. R; CLACK, G; MALONE, M; COUMANS, F. A. W; TERSTAPPEN, L. W. M. M (International journal of oncology, 2011)
A validated assay for the enumeration of circulating melanoma cells (CMCs) may facilitate the development of more effective therapies for metastatic melanoma patients. In this study CD146+ cells were immunomagnetically enriched from 7.5 ml of blood. Isolated cells were fluorescently stained with DAPI, anti-molecular weight melanoma-associated antigen (HMW-MAA), anti-CD45 and CD34 and Ki67. CMCs were identified as CD146+, HMW-MAA+, CD45-, CD34-, Ki67-/+ cells. Eighty-eight percent of spiked SK-MEL28 cells in 7.5 ml blood were recovered. In all 55 healthy donors ≤1 CMCs were detected in 7.5 ml of blood. A retrospective analysis was conducted comparing CMC counts and overall survival in 79 blood samples from 44 melanoma patients. CMCs ranged from 0 to 8,042 per 7.5 ml. Two or more CMCs were detected in 18 (23%) of the patients and 30-100% (mean 84%) of the CMCs expressed the proliferation marker Ki67. Patients with ≥2 CMCs per 7.5 ml of whole blood, as compared with the group with <2 CMCs, had a shorter overall survival (2.0 months vs. 12.1 months, P=0.001).